Surveillance der Gesundheit und primärmedizinischen Versorgung von Asylsuchenden in Aufnahmeeinrichtungen: Konzept, Entwicklung und Implementierung - Nöst, Stefan; Jahn, Rosa; Aluttis, Frank; Erdmann, Stella; Qreini, Markus; Bozorgmehr, Kayvan (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2019)
BackgroundReliable data on health and primary care among asylum seekers in reception centres are not routinely available, but required to plan needs-based healthcare services.ObjectivesTo present the concept, development, and implementation of a routine surveillance system in reception centres for asylum seekers.MethodsIn the scope of the project PRICARE, medical records in reception centres were standardized and digitized, and continuous surveillance was enabled by means of suitable IT infrastructure. The core elements of the surveillance system were developed in three project phases using an iterative and participative design. Funding: Federal Ministry of Health (Grant no. 2516FSB415).ResultsForming the basis for the surveillance, the electronic health record Refugee Care Manager® (RefCare®) was developed and gradually implemented in 13 reception centres in three federal states. For implementing the tool in daily care routines, IT infrastructure was implemented in all sites and a legally required data protection concept was established. An indicator set was developed and agreed upon for the surveillance, comprising a total of 64 indicators in four domains: morbidity, processes of care, quality of care, and syndromic alerts.ConclusionsFor the first time in Germany, a harmonized infrastructure spanning federal states was implemented in healthcare settings ensuring medical documentation and surveillance of health and healthcare of asylum seekers in conformity with data protection requirements. The surveillance is feasible; the long-term benefits of routine surveillance and research within the network will be assessed in the future.
Gesehen am 29.07.2019